2018
DOI: 10.2139/ssrn.3275988
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Affect in the Structural Mere Exposure Effect

Abstract: This paper investigates the characteristics of the affective component in the structural mere exposure effect (SMEE). Two approaches are consideredfluency attribution approach (FA) and affect as predictive efficiency approach (APE)within a predictive coding framework. Using the artificial grammar learning and affective priming paradigms, we demonstrate that a violation of implicitly learned regularities elicits an automatic negative affective response. This result suggests that SMEE can be observed without any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Future studies could also investigate additional characteristics of the revealed EC effect, such as its automaticity or controllability. For instance, in affective-priming tasks, stimuli with emotional valence automatically enhance the detection of stimuli with the same valence (Fazio, Sanbonmatsu, Powell, & Kardes, 1986; Ivanchei & Asvarisch, 2018). Using the present paradigm, participants might undergo an affective-priming task in which primes could be new strings that follow the positive or the negative grammar.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could also investigate additional characteristics of the revealed EC effect, such as its automaticity or controllability. For instance, in affective-priming tasks, stimuli with emotional valence automatically enhance the detection of stimuli with the same valence (Fazio, Sanbonmatsu, Powell, & Kardes, 1986; Ivanchei & Asvarisch, 2018). Using the present paradigm, participants might undergo an affective-priming task in which primes could be new strings that follow the positive or the negative grammar.…”
Section: Discussionmentioning
confidence: 99%
“…Schematic expectations for music, according to the predictive-coding model, can unfold at multiple levels, whether they be stylistic (hip-hop, jazz), structural (melody, tonality), temporal (rhythm, meter), and/or acoustic (pitch, timbre) factors (Guo & Koelsch, 2016; Huron, 2006; Justus & Bharucha, 2001; Margulis, 2014). The predictive-coding model can account for the mere-exposure effect by positing that repeated exposure increases the efficiency of predictions (Ivanchei & Asvarisch, 2018), resulting in increased liking of stimuli that carry predictive value (Braem & Trapp, 2019).…”
mentioning
confidence: 99%